Análise de parâmetros termográficos para inspeção de fachadas com revestimento cerâmico - Batista, Joana Sueveny Barbosa (2023)
The facade of a building, besides being an aesthetic element, is the first protective barrier against physical and chemical agents, making it susceptible to the presence of pathological manifestations. The difficulty in detecting these manifestations makes preventive maintenance difficult, and may cause deterioration of the coating. Conventional inspection techniques are often insufficient to detect these anomalies, so the infrared thermography comes as a key agent for this detection, but depending on the condition where the inspection is performed the technique is not able to generate good assertiveness. In order to improve it, this study analyzed thermographic parameters in inspections of facades with ceramic tiles, seeking more assertive methods and enabling rapid inspection and integrity analysis of construction systems of facades clad with ceramic tiles. For this, rectangular specimens were made with ceramic tiles of different colors, defects of different sizes were introduced in the center of the pieces simulating the lack of adhesive mortar and a thermographic analysis was done in the heating and cooling cycles, using thermographs of different resolutions, varying distances and viewing angles during the extraction. At the end it was possible to notice that the defect region presented a lower temperature than the surrounding area, that for larger viewing angles, the thermograms obtained lost precision, but for small angles the results were still satisfactory, and that the adjustment of the temperature scale allowed a better visualization of defects. Therefore, the practicality and ease that the thermographic inspection technique brings could be assertive with the refinement of the parameters.